THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, JOB SATISFECTION AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN HOSPITAL EMPLOYEES LANGSA REGIONAL GENERAL - Ira Safitri; Yanita; Ibrahim Qamarius; Sullaida (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study was conducted to examine the influence of Transformational Leadership, Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior in Langsa Regional General Hospital. This type of research uses a quantitative method, data collection uses a questionnaire containing questions and statements by distributing the information of the employees concerned at the Langsa Regional General Hospital. The population in this study are employees with civil servant status at the Langsa Regional General Hospital which totals 547 employees. Meanwhile, the number of samples in this study is 72 employees. The data analysis method used is a multiple linear regression analysis technique using SPSS 26. Data analysis uses classical assumption tests, partial tests (t-tests) and determination coefficient tests. The results of the study show that Transformational Leadership, Job Satisfaction and Organizational Commitment have a positive and significant effect on Organizational Citizenship Behavior in Langsa Regional General Hospital Employees.